Surgical treatment of lacrimal duct obstruction – an overview - Kwiecińska, Anna; Turczynowska, Magdalena; Woś, Małgorzata; Mackiewicz, Jerzy (Klinika Oczna / Acta Ophthalmologica Polonica, 2018)
Patients with lacrimal ducts obstruction that cause persistent lacrimation or inflammation are a common problem in ophthalmic practice. Surgery often is the only effective treatment method. External, transnasal or transcanalicular dacryocystorhinostomy is the primary surgical treatment for excessive tearing due to lacrimal duct occlusion. New surgical techniques, using laser or ultrasound energy, are being introduced. It is impossible to determine unequivocally which of these methods is the most effective. Each of them has advantages and disadvantages, and the most important stage throughout the treatment process is a comprehensive medical history, diagnosis and eligibility assessment for the appropriate type of surgery. All methods either provide a removal of obstacles or create a new lacrimation pathway. This article provides an overview of surgical methods used in the obstruction of upper and lower lacrimal pathways.